Randomized Trial of Aspirin Versus Warfarin After Transcatheter Aortic Valve Replacement in Low-Risk Patients. (January 2021) - Rogers, Toby; Shults, Christian; Torguson, Rebecca; Shea, Corey; Parikh, Puja; Bilfinger, Thomas; Cocke, Thomas; Brizzio, Mariano E.; Levitt, Robert; Hahn, Chiwon; Hanna, Nicholas; Comas, George; et al.
Abstract : Background: The optimal antithrombotic regimen after transcatheter aortic valve replacement remains unclear. Methods: In this randomized open-label study, low-risk patients undergoing transfemoral transcatheter aortic valve replacement at 7 centers in the United States were randomized 1:1 to low-dose aspirin or warfarin plus low-dose aspirin for 30 days. Patients who could not be randomized were enrolled in a separate registry. Computed tomography or transesophageal echocardiography was performed at 30 days. The primary effectiveness end point was a composite of the following at 30 days: hypoattenuated leaflet thickening, at least moderately reduced leaflet motion, hemodynamic dysfunction (mean aortic valve gradient ≥20 mm Hg, effective orifice area ⩽1.0 cm 2, dimensionless valve index <0.35, or moderate or severe aortic regurgitation), stroke, or transient ischemic attack. Results: Between July 2018 and October 2019, 94 patients were randomly assigned, 50 to aspirin and 44 to warfarin plus aspirin, and 30 were enrolled into the registry. In the intention-to-treat analysis of the randomized cohort, the composite primary effectiveness end point was met in 26.5% for aspirin versus 7.0% for warfarin plus aspirin ( P =0.014; odds ratio, 4.8 [95% CI, 1.3–18.3]). The rate of hypoattenuated leaflet thickening was 16.3% for aspirin versus 4.7% for warfarin plus aspirin ( P =0.07; odds ratio, 4.0 [95% CI, 0.8–20.0]). There was no excess bleeding at 30 days with anticoagulation. In the as-treated analysis of pooled randomized and registry cohorts, the rate of hypoattenuated leaflet thickening was 16.7% for aspirin versus 3.1% for warfarin plus aspirin ( P =0.011; odds ratio, 6.3 [95% CI, 1.3–30.6]). Conclusions: In low-risk transcatheter aortic valve replacement patients, anticoagulation with warfarin may prevent transcatheter heart valve dysfunction in the short term without excess bleeding. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03557242. Abstract : Supplemental Digital Content is available in the text.